2007
DOI: 10.1016/j.jvs.2007.03.053
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial comparing endovenous laser ablation of the great saphenous vein with high ligation and stripping in patients with varicose veins: Short-term results

Abstract: This study suggests that the short-term efficacy and safety of EVL and HL/S are similar. Except for slightly increased postoperative pain and bruising in the HL/S group, no differences were found between the two treatment modalities. The treatments were equally safe and efficient in eliminating GSV reflux, alleviating symptoms and signs of GSV varicosities, and improving quality of life. Long-term outcomes, particularly with respect to recurrence rates, shall be investigated in future studies, including the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
225
6
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(255 citation statements)
references
References 26 publications
17
225
6
7
Order By: Relevance
“…A series of recently published reviews in peer-reviewed journals have evaluated either individual techniques or a combination of EVLA, RFA and FS. [46][47][48][49][50][51] All reviews have suggested that these treatments may offer viable alternatives to traditional techniques; there is a non-significant difference in favour of surgery in terms of recurrence, but a significant difference in favour of the minimally invasive techniques in terms of technical failure. Serious adverse events were found to be rare.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A series of recently published reviews in peer-reviewed journals have evaluated either individual techniques or a combination of EVLA, RFA and FS. [46][47][48][49][50][51] All reviews have suggested that these treatments may offer viable alternatives to traditional techniques; there is a non-significant difference in favour of surgery in terms of recurrence, but a significant difference in favour of the minimally invasive techniques in terms of technical failure. Serious adverse events were found to be rare.…”
Section: Discussionmentioning
confidence: 99%
“…Other important outcomes such as ulceration were rarely reported. Six reviews, [46][47][48]50,51,166 a clinical practice guideline 26 and a cost-effectiveness analysis 136 have been published since 2007 on this topic. One meta-analysis, by Leubke et al, 47 evaluated RFA alone and that by Jia et al 46 evaluated the efficacy and safety of FS alone.…”
Section: Statement Of Principal Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Over recent years, many centers all over the world have adopted endovenous treatment by thermal ablation of the great saphenous vein (GSV) with lasers and many of them consider it the first choice option for treatment of varicose veins, primarily because of the reduced incidence of adverse events during the postoperative period. 4 The laser's principal mechanism of action is provocation of a thermal reaction, which can be controlled by adjusting several physical parameters, such as wavelength, type of administration of energy, and quantity of energy per unit of surface area (fluence, expressed in Joules per square centimeter [J/cm 2 ]), which are dependent on power, duration of pulse, and surface area. The importance of this subject has prompted many studies to discuss the ideal power settings, energy density, wavelength, and laser fiber types for achieving the final objective of endovenous thermoablation.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] Recently, new generation lasers with longer wavelengths, such as 1470 nanometers (nm), and different types of fiber optics, such as radial fibers, have begun to be adopted and are achieving even more promising results. 4,[16][17][18] The primary objective of this study is to report results of treatment for superficial venous insufficiency using a 1470 nanometer (nm) diode laser.…”
mentioning
confidence: 99%